2000
DOI: 10.1073/pnas.97.8.4221
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of α-lactalbumin to a protein inducing apoptosis

Abstract: In this study ␣-lactalbumin was converted from the regular, native state to a folding variant with altered biological function. The folding variant was shown to induce apoptosis in tumor cells and immature cells, but healthy cells were resistant to this effect. Conversion to HAMLET (human ␣-lactalbumin made lethal to tumor cells) required partial unfolding of the protein and a specific fatty acid, C18:1, as a necessary cofactor. Conversion was achieved with ␣-lactalbumin derived from human milk whey and with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
440
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(461 citation statements)
references
References 33 publications
17
440
0
4
Order By: Relevance
“…In addition, α-lactalbumins form stable folding intermediates when Ca 2+ is released [23]. We have shown that the partially unfolded form of the human protein attains a new function when bound to oleic acid [1]. HAMLET kills tumor cells in vitro and the anti-tumor activity is retained in vivo, in a brain tumor model and in patients with skin papillomas [24,25].…”
Section: Can Hamlet-like Complexes Be Formed From Casein If Oleic Acimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, α-lactalbumins form stable folding intermediates when Ca 2+ is released [23]. We have shown that the partially unfolded form of the human protein attains a new function when bound to oleic acid [1]. HAMLET kills tumor cells in vitro and the anti-tumor activity is retained in vivo, in a brain tumor model and in patients with skin papillomas [24,25].…”
Section: Can Hamlet-like Complexes Be Formed From Casein If Oleic Acimentioning
confidence: 99%
“…HAMLET 1 (human α-lactalbumin made lethal to tumor cells) is a complex of apo α -lactalbumin and oleic acid (C18:1) [1] which kills tumor cells while healthy cells are spared. The lethal effect on tumor cells was discovered in a casein fraction, obtained after low pH precipitation of human milk [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, new strategies to kill cancer cells by nonapoptotic mechanisms have flourished during the past decade, and many inducers of alternative caspase-independent cell death pathways have been identified (3)(4)(5)(6). Among them is a lipid:protein complex composed of oleic acid and human α-lactalbumin that was originally purified from human milk and termed HAMLET (Human Alpha-lactalbumin Made LEthal to Tumor cells) based on its ability to effectively kill transformed cells while leaving nontransformed cells largely unaffected (7,8). In addition to the broad antitumor activity in vitro, the therapeutic effect of HAMLET has been confirmed in a human glioblastoma xenograft model in rats as well as in human patients with skin papillomas and bladder cancer (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…But the protein also has very interesting properties. In 2000 Svensson and colleagues [12] showed that, under low calcium conditions α-lactalbumin could bind a specific fatty acid, C18:1, and adopt a altered conformation that induced apoptosis in tumor cells but not in normal cells. This altered protein was called HAMLET (human a-lactalbumin made lethal to tumor cells).…”
mentioning
confidence: 99%